First Nations Teenaged Female Lone Parent Families in Canada: Recognizing Family Diversity and the Importance of Networks of Care - Quinless, Jacqueline M. (International Indigenous Policy Journal, 2013)
Using semi-custom data tabulations from the 2006 Census of Population, this article provides a brief statistical description of the socio-economic conditions of female First Nations teenaged lone parents aged 15 to 19 years in Canada. It examines existing formal and informal social and economic support systems available to First Nations lone mother families in multiple family households. These support systems where compared to First Nations lone mothers in single family households as a way to shed light on the varying degrees that informal networks of care may be available to First Nations lone mothers living on reserve, as compared to those living off reserve, who access varying degrees of support from extended family members for the care and nurturing of their children. Despite the dominant Westernized view of the negative impacts that teenaged lone parenting can have on women and their children, this article illustrates that there seems to be a culturally interrelated system, or “networks of care,” available to these women. Such networks of care often have been overlooked in research on lone parenting. There remains much diversity among Aboriginal lone parent families when one accounts for factors such as age of the parent, number of children, living on or off reserve, education, employment, and income. Therefore, the assumption that the social and economic disadvantage of becoming a teenaged lone parent will result in the same circumstances and place all teenaged lone parents at the same “disadvantage” is not necessarily accurate, at least in the First Nation context.